INVESTIGATION LOW STOCK ACCURACY USING FAILURE MODE AND EFFECT ANALYSIS STUDY AT PT. XYZ PHARMACY - Nurdiansyah, Dandi; Rinaldi, Dikdik; Baharudin, Ikhsan; Purwanto, Ahmad Jaka; Destiano, Muhammad Andito; Rochman, Didit Damur (CENTRAL ASIA AND THE CAUCASUS, 2022)
Failure Mode and Effect Analysis (FMEA) is a method used to identify the risk of failure. This paper aims to identify the factors that can affect the accuracy of the data in the warehouse of the pharmaceutical company PT. XYZ Pharmacy is located in Bandung, Indonesia. Inventory data accuracy refers to the consistency between the actual amount of inventory and the amount of inventory recorded in the system. The results showed that the highest RPN value in FMEA was 336 and based on randomly selected sample data showed that the largest difference between stock and actual reached 48 pcs. Based on the identification results that have been carried out, the main cause of data accuracy failure is caused by the activity of borrowing goods from the warehouse to the user. Judging from the existing SOPs, it is known that there is no more detailed form of releasing goods so that the control of recording the expenditure of goods is still not good. Therefore, the author proposes to eliminate the process of borrowing goods by making policies or standard operating procedures related to Work Order Forms (WO). This WO serves to become a record issue for warehouse documentation, if there is a difference in the stock of goods in the warehouse, the cause of the difference will be known from the WO which is integrated with the CWorks system. This policy is expected to minimize or even eliminate the occurrence of stock mismatches or lack of stock accuracy.